Linieritas Integral Henstock-Pettis pada Ruang Euclide Rn - Rahman, Hairur (Mathematics Department, Maulana Malik Ibrahim State Islamic University of Malang, 2010)
In this paper we study Henstock-Pettis integral on the Euclidean space â„œn. We discuss some properties Linear integrable